Challenges of the Education System in Indonesia - Antoni, Jono; Hidayah, Jumatul; Harmi , Hendra; Ifnaldi, Ifnaldi; Hajja Ristianti, Dina (Yayasan Corolla Education Centre, 2025)
This research explores the multifaceted challenges in Indonesia’s education system, particularly within the national and Islamic education sectors. Using a qualitative library research approach, the study analyzes relevant academic sources, expert opinions, and policy documents to identify core issues and potential strategies. Data analysis is conducted through thematic content analysis, enabling the identification of recurring patterns, concepts, and policy implications across the selected literature. Findings reveal that in the VUCA era, Indonesia's education system faces challenges in economic transformation, socio-cultural shifts, labor market demands, and alignment with Indonesia’s 2045 vision. Expert perspectives emphasize the need for cyber-based learning models and a balanced integration of technology and human values. Additionally, the Policy Forum on Education (PFoE) outlines eight major challenges, such as teacher competence, curriculum adaptability, digitalization, and inclusivity. In Islamic education, core issues include limited institutional capacity, weak graduate recognition, and inadequate quality assurance. The research highlights strategies to improve Islamic education through institutional strengthening, curriculum standardization, and quality service delivery. These findings underscore the urgent need for an integrated, adaptive, and inclusive educational framework to prepare Indonesia’s future generations.